APPLICATION TO KNOW NUMBERS CHILDHOOD AND NUMERACY USING MACROMEDIA FLASH 5.0 - Herjun Kurniawan; Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2003)
In accordance with this writing, it can be concluded that the application usingMacromedia Flash which is made by the author, it is expected in teaching arithmeticto young children experiencing no more mistakes so that young children canrecognize and name-digit numbers correctly. By using this application may be helpfulin education especially in numeracy lessons for children under five.